Temozolomide (Temodar) - Wesolowski, J.R. (AJNR Am J Neuroradiol, 2010)
Temozolomide, an oral alkylating agent, is a commonly used medicine in the treatment of anaplastic astrocytoma and glioblastoma multiforme. This paper will present the mechanism of action as well as the clinical role for this chemotherapeutic drug.